On Negligibility of Asset-Specific Risks at the Capital Market Equilibrium - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 1983)
Examines an economic environment in which asset-specific risk components is not compensated at the capital market equilibrium. Capital asset pricing model; Asset allocation; Characterization of mean-variance model.